2022
DOI: 10.1117/1.jei.31.6.060901
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and analysis on underwater image enhancement methods, datasets, and evaluation metrics

Abstract: valuable resources that exist beneath Earth's surface. Underwater exploration requires enhanced images that are obtained using enhancement methods. So, it is important that underwater image enhancement (UIE) methods work well in terms of performance and accuracy. As a result, research in UIE has increased in the past few years. An extensive survey is conducted on existing UIE methods along with their broad classification, underwater datasets, and evaluation metrics, respectively. The experimental analysis is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…Zhang et al 6 proposed an extended multi-scale Retinex-based UIE method, which processed the underwater images in CIELAB color space. 7 Liu and Chau 8 observed that the dark channel of underwater images tended to zero and designed a UIE method based on contrast enhancement. Peng et al 9 proposed an underwater scene depth estimation method called IBLA based on image blurring and light absorption.…”
Section: Traditional Methodsmentioning
confidence: 99%
“…Zhang et al 6 proposed an extended multi-scale Retinex-based UIE method, which processed the underwater images in CIELAB color space. 7 Liu and Chau 8 observed that the dark channel of underwater images tended to zero and designed a UIE method based on contrast enhancement. Peng et al 9 proposed an underwater scene depth estimation method called IBLA based on image blurring and light absorption.…”
Section: Traditional Methodsmentioning
confidence: 99%
“…In order to prove the de-fogging effect of the improved dark channel de-fogging algorithm in this paper, the de-fogging effect was compared with that of He Keming, Fattle and Tan respectively. Peak signal-to-noise ratio (PSNR) and structural similarity (SSIM [9,10] ) were used to measure the image quality after de-fogging. The peak signal-to-noise ratio (PSNR) is used to express the ratio between the maximum possible power of a signal and the power of destructive noise that affects the fidelity of its representation.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…According to the "center-periphery difference", the difference between the images of different layers of the pyramid is calculated to obtain the brightness, color and direction feature images. Before calculating the difference value, the method of reducing the difference value of the image is adopted to unify the size of the image [21]. The calculation method is as follows.…”
Section: Visual Saliency Analysismentioning
confidence: 99%